2011
DOI: 10.5205/reuol.1262-12560-1-le.0509201119
|View full text |Cite
|
Sign up to set email alerts
|

Risk for phlebitis in the inpatient unit of hospital emergency and trauma

Abstract: Objective: to analyze the occurrence of risk factors for phlebitis in the clinic of the Hospital Emergency and Trauma, Petrolina – Pernambuco, Brazil. Methodology: field research, observational, descriptive and quantitative, its population was inpatients in medical clinic and use of peripheral venous access; 225 accesses the sample quantified, reported daily in September 2010, using a questionnaire on risk factors for phlebitis. Data collection took place after approval by the Ethics Committee for Studies of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
6

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…Therefore, keeping the dressing clean and identified, using micropore, observing fluency and integrity, and avoiding unsafe venous access are safe practices that must be followed by the Nursing team. 12,21,26 One study found that the highest frequency of adverse events occurred in an intensive care unit and 85% were related to the patients themselves. 26 A survey that evaluated 221 peripheral venous accesses identified 42 phlebitis, relating this event to the anatomical structure, and in the veins of the hand's back, there was a higher incidence, with 52.5%, and in the median cubital region, the lowest, with 4.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, keeping the dressing clean and identified, using micropore, observing fluency and integrity, and avoiding unsafe venous access are safe practices that must be followed by the Nursing team. 12,21,26 One study found that the highest frequency of adverse events occurred in an intensive care unit and 85% were related to the patients themselves. 26 A survey that evaluated 221 peripheral venous accesses identified 42 phlebitis, relating this event to the anatomical structure, and in the veins of the hand's back, there was a higher incidence, with 52.5%, and in the median cubital region, the lowest, with 4.9%.…”
Section: Resultsmentioning
confidence: 99%
“…A prevalência de flebite pode variar de 2,7 a 64,9% [6][7][8][9][10][11] ; discrepância que pode ser explicada pela dificuldade em padronizar o monitoramento e as condutas em relação à flebite, além da dificuldade em diferenciar os graus da mesma por diferentes profissionais. Nossos resultados são semelhantes a outros estudos, com prevalência de flebite entre 24,7 e 28,0% [6][7][8] , embora menores que outros estudos que mostram valores entre 41,2 e 42,0% 9,10 .…”
Section: Discussionunclassified
“…Nossos resultados são semelhantes a outros estudos, com prevalência de flebite entre 24,7 e 28,0% [6][7][8] , embora menores que outros estudos que mostram valores entre 41,2 e 42,0% 9,10 . O grau 2 de flebite, como encontrado por nós, parece ser o mais comumente encontrado na literatura com prevalências de 35,1 a 40,0% 6,8,11,12 .…”
Section: Discussionunclassified
See 2 more Smart Citations